POLYAMORY: THE NEED OF RECOGNITION OF NEW FAMILY ARRANGEMENTS AND GENERATION OF LEGAL EFFECTS BASED ON HUMAN RIGHTS AND ON CONCEPT OF POST-MODERN FAMILY OF THE 21ST CENTURY - De Oliveira, Caroline Buarque (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to analyze the polyamory, to define it as a family form. The research demonstrates,fulcrumin the rights and guarantees fundamental, the necessity of recognition a new familiar design and generation of legal effects. In according to theperspectiveContemporary of Civil Constitutional Law, is made an analysis of the evolution of family models and concepts, bringing influences of fundamental rights and human rights. Based on a deductive methodology, it is defended a concept own of family. Starting from polyamory, the characteristics of a new family model were highlighted. The research brings the Brazilian Judiciary's understanding around polyamory’s recognition possibility. From the investigation, it is possible to conclude that polyamory can be understood as a family form and therefore, must be protected by the State. In studies future, investigators will able to examine the multiparenthood as a precedent for judicial recognizing of polyamory in Brazil.